2021
DOI: 10.4103/jomfp.jomfp_441_20
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire-based survey regarding the opinion of general pathologists on the need for oral pathology services

Abstract: Context: Oral and maxillofacial pathology (OMFP) is a subspecialization having a masters course in India. Due to lesser number of oral pathologists in the country, the biopsy material from the head and neck is catered to by the general pathologist. Aim: This survey was conducted to acquire responses from general pathologists and gathering knowledge on their perspective of oral pathology. Methods: Pathologists at various medical institutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
(23 reference statements)
1
3
1
Order By: Relevance
“…The findings of this study provide strong support for the belief held by many general pathologists regarding the importance of oral pathologists in the diagnosis of oral pathological lesions. These results align with the study conducted by Salian and Natarajan, 3 which emphasized the importance of oral pathologists in the diagnosis of oral pathological lesions, as perceived by general pathologists. One of the key reasons for this preference is that oral pathologists undergo comprehensive training for a period of 2–4 years specifically in the field of oral pathology, which equips them with extensive knowledge and advanced skills necessary for accurate diagnosis in this specialized area.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The findings of this study provide strong support for the belief held by many general pathologists regarding the importance of oral pathologists in the diagnosis of oral pathological lesions. These results align with the study conducted by Salian and Natarajan, 3 which emphasized the importance of oral pathologists in the diagnosis of oral pathological lesions, as perceived by general pathologists. One of the key reasons for this preference is that oral pathologists undergo comprehensive training for a period of 2–4 years specifically in the field of oral pathology, which equips them with extensive knowledge and advanced skills necessary for accurate diagnosis in this specialized area.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we observed that more than half of the general pathologists did not refer cases of odontogenic cysts and tumors to oral pathologists. This contrasts with a previous study 3 where these pathologies were frequently referred for consultation with oral pathologists. The limited exposure of general pathologists to oral and maxillofacial region pathologies could explain this discrepancy, leading to uncertainty and a lower rate of referrals in such cases.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations